1987
DOI: 10.1111/j.1600-079x.1987.tb00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Immunoreactive Melatonin, Estradiol, Progesterone, Follicle Stimulating Hormone, and β‐Human Chorionic Gonadotropin During Pregnancy and Shortly After Parturition in Humans

Abstract: Plasma concentrations of immunoreactive melatonin, estradiol, progesterone, follicle stimulating hormone (FSH), and beta-human chorionic gonadotropin (beta hCG) were studied between 1000 and 1230 h in 105 Chinese females during six periods of normal pregnancy and 1-5 min after normal delivery. We have also examined the midday levels of immunoreactive melatonin in the cord blood of fetuses and plasma collected 1-5 min after and 24 h after delivery from their mothers. Concentrations of hormone immunoreactivities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
1
22
0
2
Order By: Relevance
“…There are some indications that hormones of the reproductive system can affect the biochemistry and histology of the pineal gland [22,23] and that gonad otropins and sex steroids may play a regulatory role on pineal melatonin secretion [30,34]. Thus, it has been re ported that gonadectomy or steroid treatment changed the activity of hydroxyindole-O-methyltransferase [3,4], that circulating melatonin changes during the menstrual cycle [34] and after gonadotropin administration [30] and that FSH may increase plasma melatonin concentrations in pregnant women [20]. Also, hyperprolactinemia in rats significantly decreases pineal gland melatonin content [31].…”
Section: Discussionmentioning
confidence: 99%
“…There are some indications that hormones of the reproductive system can affect the biochemistry and histology of the pineal gland [22,23] and that gonad otropins and sex steroids may play a regulatory role on pineal melatonin secretion [30,34]. Thus, it has been re ported that gonadectomy or steroid treatment changed the activity of hydroxyindole-O-methyltransferase [3,4], that circulating melatonin changes during the menstrual cycle [34] and after gonadotropin administration [30] and that FSH may increase plasma melatonin concentrations in pregnant women [20]. Also, hyperprolactinemia in rats significantly decreases pineal gland melatonin content [31].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural changes have been described in the pineal gland of rats [Satodate et al, 1980;Karasek et al, 1982], moles [Pevet and Smith, 1975], guinea pigs [Vollrath and Schmidt, 1969], and sows [Wyrzykowski et al, 1987]. Likewise, pineal activity has been related to pregnancy by biochemical studies performed in rats [Tigchelaar and Nalbandov, 1975] and humans [Pang et al, 1987]. It has been suggested that the pineal gland in rats may be involved in the synthesis and release of gonadotropins.…”
Section: Introductionmentioning
confidence: 97%
“…созревание шейки матки и раскры-тие маточного зева наблюдается с большей ча-стотой между 24.00 и 05.00 часами ночи [43,45]. Показана взаимосвязь между высоким уровнем мелатонина в амниотической жидкости, в крови матери и плода, что указывает на важную роль и плодового мелатонина в наступлении родов [47,68,73,76,101].…”
unclassified